Comparison between Conventional Extraction and Ultrasound Assisted Extraction of Labisia Pumila Sp. in 25-L MobileExtractor using Water as Solvent of Extraction - Nuri Adilah Nashrulmillah, Idris; Ahmad Ziad, Sulaiman (AIDIC Servizi, 2017)
Labisia pumila (Kacip Fatimah) is a medicinal plant enriches with functional compound and bioactive properties which can promote and provide a beneficial effect to human health. An antioxidant, gallic acid is widely obtained from natural sources such as Labisia pumila. To extract this bioactive compound, appropriate techniques of extraction are needed to fully utilise the resources without damaging the crude quality. Ultrasound technique is recognised for potential industrial application in the phytopharmaceutical extraction for a broad range of herbals. The aim of this study was to investigate the performance between conventional extraction and ultrasound-assisted extraction (UAE) in 25 L mobile extractor using four sonication duty cycle regimens; 40%, 50%, 80% and 100% in extraction bioactive compound from Labisia pumila. Other parameters such as temperature (50⁰C, 60⁰C, 80⁰C, and 100⁰C), the sample-to-water ratio (1:20 and 1:40) and duration of extraction (1-10h) were also investigated. For the conventional method, the same parameters were conducted, but without the engagement of ultrasound irradiation. In all experiments, water was used as the solvent for the extraction. The yields of gallic acid from Labisia pumila was identified and quantify using HPLC-DAD. The optimum gallic acid, 133.25 ± 3.60 mg GAE/g dry weight was gained at conditions combination of 50% duty cycle, the temperature at 60⁰C, the sample-to-water ratio at 1:20 (kg/L), and 8h of extraction time. The study proved sonication regimes of ultrasound enhance extraction yield of gallic acid from Labisia pumila up to 1.23-fold compared to the conventional method